Circulating miR155 expression level is positive with blood pressure parameters: Potential markers of target-organ damage. (2nd April 2016) - Huang, Yuqing; Chen, Jiyan; Zhou, Yingling; Tang, Songtao; Li, Jie; Yu, Xueju; Mo, Yujing; Wu, Ying; Zhang, Ying; Feng, Yingqing
ABSTRACT: Objectives : The aim of this study is to evaluate the relationship of miR155 with office and ambulatory blood pressure (BP) parameters and left ventricular hypertrophy (LVH) in patients with hypertension and healthy controls. Methods : We assessed the expression level of the miR155 in 50 patients with essential hypertension and 30 healthy individuals. All patients underwent two-dimensional echocardiography, office BP monitoring and ambulatory blood pressure monitoring (ABPM). Quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) was used to evaluate the expression of selected miR155. The miR155 correlations between BP parameters and left ventricular mass index (LVMI) were assessed using the Spearman correlation coefficient. Results : We observed higher expression level of miR155 (33.22 ± 2.59 vs. 27.30 ± 1.76; p < 0.001) in hypertensive patients compared with healthy control individuals, as well as in LVH to nLVH group (33.00 ± 2.78 vs. 27.28 ± 1.76; p < 0.001). MiR155 expression level showed significant positive correlations with office measurement of systolic blood pressure (SBP) ( r = 0.634, p < 0.001), diastolic blood pressure (DBP) ( r = 0.222, p < 0.05), pulse pressure (PP) ( r = 0.564, p < 0.001), respectively. And explored miR155 expression level in relation to 24-h ABPM parameters showed significant positive correlation with 24 h mean SBP ( r = 0.67, p < 0.001), 24 h mean DBP ( r = 0.257, p < 0.05), 24 h mean PP ( r = 0.597, p < 0.001), respectively, as well as with LVMI ( r = 0.591, p < 0.001). Conclusion : Circulating miR155 may possibly represent potential non-invasive marker of hypertension and target organ damage (TOD) in essential hypertensive patients.